A quantitative criterion to predict atomic disordering during high velocity nanoparticle impact. (September 2022) - Chitrakar, T.V.; Becker, Michael F.; Kovar, Desiderio
Abstract: Particle deformation at impact is a critical parameter for film formation using aerosol deposition processes for sub-micron particles. Here we study the necessary criteria to initiate atomic disorder during particle impact that can lead to deformation via viscous flow. Molecular dynamics simulations were conducted to test the hypothesis that disordering of individual silver atoms occurs under non-uniform, high strain rate loading when a critical potential energy/atom (PE/atom) of −2.72 eV is exceeded. To test this hypothesis, simulations of Ag nanoparticles impacting a flat Ag substrate were conducted for impact velocities of 100, 300, and 600 m/s, and the PE/atom and the atomic configurations for atoms positioned at different locations within the nanoparticles were tracked over time. The results showed that atoms that disorder or do not disorder could be correctly predicted by the PE/atom. A statistically varying time differential was observed between the time amorphization was predicted and when it occurred. For the small fraction of the atoms that were borderline cases, the PE/atom and two measures of atomic disorder did not agree. The physical causes for the time differentials between predicted and observed disordering and the accuracy of prediction of disordering are discussed. Highlights: MD simulations of Ag nanoparticle deposition show local solid-state disordering. When the atom's potential energy exceeds −2.72 eV, then disordering is predicted. Inhomogeneous loading with nonuniform strain rates and strain states is present. Disorder is correctly predicted for substantially more than 90% of the study atoms.